Direct Full-Length RNA Sequencing Reveals an Important Role of Epigenetics During Sexual Reversal in Chinese Soft-Shelled Turtle - Zhou, Tong; Chen, Guobin; Chen, Meng; Wang, Yubin; Zou, Guiwei; Liang, Hongwei (Frontiers in Cell and Developmental Biology, 2022)
Sex dimorphism is a key feature of the Chinese soft-shelled turtle (Pelodiscus Sinensis). The males (M) have higher economic value than females (F) due to wider calipash and faster growth. Exogenous hormones like estradiol and methyltestosterone can induce sexual reversal to form new phenotypes (pseudo-female, PF; pseudo-male, PM) without changing the genotype. The possibility of inducing sexual reversal is particularly important in aquaculture breeding, but the underlying biological mechanisms remain unclear. Here we applied a direct RNA sequencing method with ultralong reads using Oxford Nanopore Technologies to study the transcriptome complexity in P. Sinensis. Nanopore sequencing of the four gender types (M, F, PF, and PM) showed that the distribution of reading length and gene expression was more similar between same-sex phenotypes than same-sex genotypes. Compared to turtles with an M phenotype, alternative splicing was more pronounced in F turtles, especially at alternative 3’ splice sites, alternative 5’ splice sites, and alternative first exons. Furthermore, the two RNA methylation modifications m5C and m6A were differentially distributed across gender phenotypes, with the M type having more modification sites in CDS regions, but fewer modification sites in 3’UTR regions. Quantitative analysis of enriched m6A RNAs revealed that the N6-methylated levels of Odf2, Pacs2, and Ak1 were significantly higher in M phenotype individuals, while the N6-methylated levels of Ube2o were reduced after sexual reversal from both M and F phenotypes. Taken together, these findings reveal an important role of epigenetics during sexual reversal in Chinese soft-shelled turtles.